African American English intensifier dennamug: Using twitter to investigate syntactic change in low-frequency forms - Jones, Taylor (Frontiers in Artificial Intelligence, 2023)
There are some linguistic forms that may be known to both speakers and linguists, but that occur naturally with such low frequency that traditional sociolinguistic methods do not allow for study. This study investigates one such phenomenon: the grammatical reanalysis of an intensifier in some forms of African American English – from a full phrase "than a mother(fucker)" to lexical word "dennamug" – using data gathered from Twitter. While state-of-the-art traditional corpora (e.g., the Corpus of Regional African American Language), contain so few tokens they can be counted on one hand, Twitter yields almost 300,000 tokens over a ten year sample period. This computational approach reveals ongoing grammaticalization, with the new intensifier associated with bare, note comparative, adjectives, and that there is seemingly stable variation correlated with the degree to which the intensifier has lexicalized. Orthographic representations of African American English on social media are shown to be a locus of identity construction and grammatical change.